A Study of Church-Affiliated Girls’ Schools in Late Qing China - YIN Yiting (Journal of Research for Christianity in China (JRCC), 2025)
Among the missionary endeavors undertaken by female missionaries in modern China, none exerted a more profound influence on Chinese women than the advancement of education. British missionary Mary Ann Aldersey established China’s first boarding school for girls in Ningbo in 1844, initiating systematic church-sponsored girls’ education in China. Aldersey served as a missionary for the Society for the Promotion of Education for Women in the East (hereafter referred to as the Society), founded in 1834. The Society also provided financial support for this school, thereby playing a pioneering role in establishing church-affiliated girls’ schools in China’s interior. Scholars have produced considerable research on Christian higher education for women in China. However, the missionary-run girls’ schools established by the Society in China during the latter half of the 19th century primarily offered elementary education. Compared to research on missionary higher education, studies on missionary primary and secondary education remain relatively underdeveloped. This paper centers on the author’s available materials concerning the Oriental Women’s Education Promotion Society to analyze the impact of elementary missionary girls’ schools established by female missionaries in late Qing China on Chinese women, particularly those from lower social strata, in terms of religion, family, and career. The study period spans from the founding of the first boarding school for girls by Miss Aldersby in 1844 to the dissolution of the Oriental Women’s Education Promotion Society in 1899.